Korekční osteotomie distálního radia - Pacovský, V; Svatoš, F (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2011)
PURPOSE OF THE STUDY: The aim of the study was to evaluate the outcomes of corrective osteotomy for malunited fractures of the distal radius, to assess the degree of correction or its loss, if it happened, after bone union, and to compare the clinical and radiographic results with the relevant literature reports. MATERIAL AND METHODS: In the period from September 2002 and October 2004, a total of 16 patients (six men and 10 women) underwent surgery for malunited fractures of the distal radius. The average patient age was 49.3 years, with a range of 23 to 73 years. For the sake of evaluation, records were made of patients' subjective feelings, objective measurements of motion range and muscle strength and exact measurements of relevant parameters on radiographs. Plain radiographs of the distal radius of both upper extremities in anteroposterior and lateral projections were made before and after surgery, and at final follow-up after osteotomy healing. The following parameters were measured: length of the radius, ulnar inclination angle and tilt of the distal articular surface of the radius. Because we evaluated our patients in retrospect, it was not always possible to find the exact values of motion range and muscle strength as they existed before surgery. Therefore, for comparison, we used the values obtained on the unhurt extremity. Corrective surgery included radius opening-wedge osteotomy with bone graft insertion and subsequent fixation with a 3.5-mm T plate. The final evaluation was based on the New York Orthopaedic Hospital Wrist Rating Scale. RESULTS The highest lengthening achieved by corrective osteotomy was 9 mm. The largest change in the ulnar inclination angle was 34 degrees. The best correction of a dorsal deformity was 24 degrees. The result evaluation was : 30 % excellent, 50 % good, and 20 % fair. DISCUSSION Corrective osteotomy of the distal radius with graft insertion is one of the options for the restoration of anatomical conditions following malunited fractures. The timing and technique of the surgical procedure were in agreement with the data reported in the literature, as well as the results achieved in this study. CONCLUSIONS: Corrective osteotomy and bone graft insertion are surgical procedures used for the treatment of malunited fractures of the distal radius. They are indicated in active younger patients with proven symptoms and correlating radiographic evidence. The surgery should be preceded by a thorough radiographic examination and pre-operative planning. Key words: distal radius fracture, bone malunion, corrective osteotomy.
Keywords: senioři; transplantace kostí; Radiography; Bone Transplantation; špatně zhojené fraktury; Radius; osteotomie; Middle Aged; fraktury vřetenní kosti; mužské pohlaví; Radius Fractures; radius; Adult; mladý dospělý; Young Adult; ženské pohlaví; radiografie; Humans; lidé středního věku; Osteotomy; dospělí; Female; Aged; Fractures, Malunited; lidé; Male